Olfactory, Taste, and Photo Sensory Receptors in Non-sensory Organs: It Just Makes Sense - Dalesio, Nicholas M.; Barreto Ortiz, Sebastian F.; Pluznick, Jennifer L.; Berkowitz, Dan E. (Frontiers in Physiology, 2018)
Sensory receptors that detect and respond to light, taste, and smell primarily belong to the G-protein-coupled receptor (GPCR) superfamily. In addition to their established roles in the nose, tongue, and eyes, these sensory GPCRs have been found in many ‘non-sensory’ organs where they respond to different physicochemical stimuli, initiating signaling cascades in these extrasensory systems. For example, taste receptors in the airway, and photoreceptors in vascular smooth muscle cells, both cause smooth muscle relaxation when activated. In addition, olfactory receptors are present within the vascular system, where they play roles in angiogenesis as well as in modulating vascular tone. By better understanding the physiological and pathophysiological roles of sensory receptors in non-sensory organs, novel therapeutic agents can be developed targeting these receptors, ultimately leading to treatments for pathological conditions and potential cures for various disease states.